Los heraldos negros: Syncretism of an inaugural work - Echevarría, Andrés (Espergesia, 2019)
César Vallejo, with his poetic work Los heraldos negros (The Black Heralds), marks a new direction in Latin American literature that until then had been influenced by the ancestry of Symbolists and Parnasians, besides the influence of Walt Whitman’s colloquialism and Rubén Darío’s modernist style. However, since his first book, the intention of accessing a localist vision has been noted and, therefore, the symbology of French origin coming from Gallic writers is displaced by Andean elements close to the author. The Vallejian syncretism proposes from the very beginning to unite several cultures: The European influence of the predominant modernism, the echoes of a nearby indigenism and the miscegenation that was proper to him as part of a continent that looked for a voice that represented him. The aim of this article is to analyse the literary proposals put forward in one of the most important works of human thought, as well as the contextual and biographical links that led to their publication.